Selection of Objects in Vilnius Guidebooks in the Nineteenth and Twentieth Century - Михайлович Лавринец, Павел (Slavistica Vilnensis, 2009)
The choice of sights described or mentioned in Vilnius guidebooks varies greatly. The article examines seventeen Lithuanian, Russian and Polish guidebooks published between 1858 and 1915, in the interwar era in 1937 and during the Soviet period. The analysis shows that the selection of objects depended heavily on the ideological, national and political interpretation of the city’s history. The criteria, which are not expressed explicitly, bespeak significance of a social function, a historical-architectural and aesthetic value, and important events and activities of outstanding figures in social, political and cultural history. The ideological and national-cultural orientations determine differences the evaluations of events and personalities, which reveals the criteria for object selection and their descriptions.